Masterchef Canada Judges’ Strategies for Giving Compliments in the Season 7 Finale - Virginia, Fanny; Ambalegin, Ambalegin (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
This descriptive qualitative research sought to examine compliment as one of the pragmatics phenomena. The object of this research is compliment strategies applied to acknowledge contestants as interlocutors. The finale episode of MasterChef Canada season 7 entitled “And the Winner of Season 7 Is…” became the data source. It got Claudio Aprile, Michael Bonacini, and Alvin Leung to challenge the finalists to show the culmination of their skills in cooking three dishes within three hours. In giving compliments to the contestants, various ways were applied to have their compliments delivered. Compliment utterances of the three judges were collected as data through observational methods and note-taking techniques. The pragmatic identity method and pragmatic competence equalizing technique were then used to analyze the collected data. To theoretically explore compliment strategies, the theory coined by Yuan (2002) was adopted. The result reported that eight out of ten strategies were employed and those were found in 23 utterances. The explicit compliments consisted of ten data, advice showed four data, explanation got three data, contrast had two data, and one data belonged to each strategy of implicit compliment, non-compliment, information question, and future reference. From the strategies, explicit compliments got the highest frequency as the judges tended to express compliments by giving direct compliments without being triggered by previous actions and leaving nothing lack of sureness. In the finale episode, compliments were frequently expressed by including the positive semantic carriers, namely “amazing”, “awesome”, “good”, “beautiful”, “like”, “love”, “elevated, “nailed”, “stop conversation”, and “great”. The frequency of giving compliments was caused by the good performance of the contestants in the Season 7 Finale. The use of compliant expressions helped the judges to express their appreciation in various ways.